The press effect - Kathleen Hall Jamieson (Oxford University Press, 2004)
How does the press fail us during presidential elections? Jamieson and Waldman show that when political campaigns side-step or refuse to engage the facts of the opposing side, the press often fails to step into the void with the information citizens require to make sense of the political give-and-take. They look at the stories through which we understand political events-examining a number of fabrications that deceived the public about consequential governmental activities-and explore the ways in which political leaders and reporters select the language through which we talk and think about politics, and the relationship between the rhetoric of campaigns and the reality of governance